You can(’t) take it with you: the anthropological analysis of the individuals from burials dated with coins (14th–15th centuries) from the mediaeval cemetery at Buftea - Știrbu, F.; Vasile, G. (Materiale și Cercetări Arheologice)
Following the preventive archaeological research carried out in 2020–2021 in the town of Buftea, the site Buftea – La Cârna/Mănești (Ilfov County) brought back into the attention of the scientific community a large mediaeval cemetery, previously discovered and studied by Aristide Ștefănescu between 1972–1982. On this occasion, 1053 burial complexes were recovered, grouped chronologically into two funerary horizons : one from the 14 th –15 th centuries and a second one from the 16 th –17 th centuries, the latter comprising graves surrounding a brick church. The current research focuses on the anthropological analysis of a sample of graves belonging to the first burial horizon, namely that of the 14 th –15 th centuries. Regarding the sampling of skeletal material, only burial complexes datable through associated coins were selected for analysis. Thus, we are dealing with 12 individual graves and five double graves. First and foremost, the research focused on determining the demographic profile of this skeletal sample, establishing the minimum number of individuals, determining the anthropological sex, and estimating the age‑at‑death of the individuals. In order to reconstruct the biological profile of the population, cranial and postcranial measurements were performed ; based on the latter, the skeletal stature and weight of the individuals could be calculated. The lifestyle of the analysed individuals was also highlighted by recording pathological changes, traumatic injuries, and skeletal and dental anomalies